The Effect of Atorvastatin Plus Ezetimibe Therapy Versus Atorvastatin Monotherapy on Clinical Outcome in Acute ST-Segment Elevation Myocardial Infaction(STEMI) - Abdul Mukid, Md; Shahabuddin, Md; Tazin, Farzana; Suhail Alam, Md; Roy Chowdhury, Partha Sarathi (Medicine Today, 2023)
Introduction: An acute ST-elevation myocardial infarction (STEMI) is an event in which transmural myocardial ischemia results in myocardial injury or necrosis. The current 2018 clinical definition of myocardial infarction (MI) requires the confirmation of the myocardial ischemic injury with abnormal cardiac biomarkers. Acute coronary syndrome is the leading cause of death in the world and this is a consequence of unstable plaque due to dyslipidemia, reviewing with elevated LDL cholesterol. Reduction in LDL-c repeated clinical outcomes in patients with the acute coronary syndrome. Objective: To assess the effect of atorvastatin plus ezetimibe therapy versus atorvastatin monotherapy on clinical outcome in acute ST-Segment Elevation Myocardial Infaction(STEMI). Materials and Methods: A cross-sectional study was performed at dept. of Cardiology, Parkview Medical College, Sylhet, Bangladesh from June to December 2022. A total of 50 patients were evaluated in the study, including 42 patients with acute coronary syndrome with LDL-c levels≥70mg/dL at Can Tho Central General Hospital, we divided randomly into 2 groups: group A: control LDL-c by atorvastatin 40mg and ezetimibe 10mg; group B: control LDL-c by atorvastatin 40mg monotherapy. Then we compared the effect of control LDL-c between two groups after 10 follow-up days. Results: 50 patients with acute coronary syndrome: 60.0% male and 40.0% female, the average age was 66.03 ± 12.06 years, 82.0% LDL- c levels ≥7 mg/dL. After 10 days of treatment, the target LDL-c concentration in the group treated with atorvastatin 40mg+ ezetimibe 10mg was 48.1%, in the group treated with atorvastatin 40mg was 29.9% (p<0.05). Conclusions: LDL-c ratio reaches the target in the treatment group by atorvastatin 40mg + ezetimibe 10mg was 48.1% in the treatment group with atorvastatin 40 mg was 29.9% (p<0.05). From the results of our study, we recommend the combination therapy of atorvastatin and ezetimibe control LDL-c in patients with acute coronary syndrome better than atorvastatin monotherapy, thus physicians to treat patients with the acute coronary syndrome should combine early atorvastatin with ezetimibe since hospitalization. Medicine Today 2023 Vol. 35(2): 99-104